2005
DOI: 10.1111/j.1365-2656.2005.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between taxonomic resolution and spatial scales of multivariate variation

Abstract: Summary 1.We investigated the effects of changes in taxonomic resolution on analyses of patterns of multivariate variation at different spatial scales for the highly diverse fauna inhabiting holdfasts of the kelp Ecklonia radiata . 2. Multivariate analyses were performed using several transformations to examine differences in spatial patterns of variation from metres up to hundreds of kilometres for composition vs. relative abundance in assemblages. 3. The greatest variability in assemblages occurred at the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(100 citation statements)
references
References 71 publications
(98 reference statements)
8
89
1
Order By: Relevance
“…Sedimentation, dispersal of propagules and post settlement processes such as competition, grazing and desiccation are potential factors that can explain variation on small spatial scales (Coleman 2002). Moreover, Anderson et al (2005a) have indicated that small-scale heterogeneity of habitat, differential settlement cues or patchy disturbance and succession may explain patchiness at smaller spatial scales. Only future manipulative experiments will provide a cause effect relationship between the high small-scale variability observed and the potential processes mentioned, but small-scale heterogeneity of habitat is the process more likely to be operating in this particular system, especially because our sampling did not consider a homogeneity of the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Sedimentation, dispersal of propagules and post settlement processes such as competition, grazing and desiccation are potential factors that can explain variation on small spatial scales (Coleman 2002). Moreover, Anderson et al (2005a) have indicated that small-scale heterogeneity of habitat, differential settlement cues or patchy disturbance and succession may explain patchiness at smaller spatial scales. Only future manipulative experiments will provide a cause effect relationship between the high small-scale variability observed and the potential processes mentioned, but small-scale heterogeneity of habitat is the process more likely to be operating in this particular system, especially because our sampling did not consider a homogeneity of the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…PRIMER6 and PERMANOVA+ (version 6.1.12 and version 1.0.2; Primer-E, Ivybridge, UK), respectively were used to conduct permutation multivariate analysis of variance (PERMANOVA) [49], and canonical analysis of principal coordinates (CAP) [50]. For this analysis sequence read data organised at the genus-level was normalised as percentages, square root transformed and a resemblance matrix created by calculation of Bray-Curtis coefficients.…”
Section: Diversity and Multivariate Analysis Of Gi Tract Microbial DImentioning
confidence: 99%
“…These studies have incorporated diverse taxa that have not all been identified to the same level of resolution and 'species' and may include many taxa identified to genus, family or even phylum (e.g. Anderson et al 2005). This problem can be overcome by testing such ideas with well-described taxa, such as annelids.…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale local processes, such as competition or predation, are likely to cause variation in populations of individual species at scales of centimetres to 100s of metres (Underwood & Chapman 1996). Largescale processes, such as historical events, biogeography, or effects of average temperature, may be readily identifiable as changes in taxa grouped into genera or families (Levin 1992) because large amounts of small-scale variability among individual species are generally thought to flatten or average out as data are accumulated over larger scales and longer times (Warwick 1988, Anderson et al 2005 such that impacts are manifest at higher taxonomic levels (Ferraro & Cole 1990, Olsgard et al 1998.…”
Section: Introductionmentioning
confidence: 99%